Growth and yield of selected forage corn hybrids and weed composition under different fertilizer application regimes - Zahid, Obaidurahman; Nazli, Muhamad Hazim; Jusoh, Mashitah; Ahmad Hamdani, Muhammad Saiful (Agri Bio Research Publishers, 2022)
Key focus for improving fertilizer use efficiency and increasing corn productivity is timing of fertilizer application at suitable crop growth stage. Therefore, a field research was conducted during 2019, at Field 15, Faculty of Agriculture, University Putra Malaysia, to quantify the effect of four fertilizer application regimes T1 (1, 3 and 4 weeks after planting–WAP), T2 (2, 4 and 6 WAP), T3 (2, 4, 6 and 8 WAP) and T4 (2, 4, 8 and 10 WAP) on growth and yield attributes of two corn varieties (GWG888 and CP888) and weed composition. The results indicated that both factors (fertilizer application regimes and varieties) significantly influenced corn growth, yield and weed composition. It was observed that T3 (application of fertilizer at 2, 4, 6 and 8 WAP) for GWG corn variety produced the highest plant height, leaf area, cob length, dry matter yield and crude protein, while it decreased NDF, ADF and lignin content compared to other treatments. Meanwhile, broad leaf weeds showed higher dominance in all fertilizer application regimes compared to grasses and sedges weed. The findings suggested that the use of fertilizer up to 8 WAP resulted in sufficient nutrients supply for flowering and after flowering stages, which improved corn growth, yield and forage quality.